(untitled) (Modern information system and technologies, 2018)
Currently, the information control service is becoming increasingly relevant in the information security market. This article gives a detailed classification of services and focuses on the peculiarities of various types of information control. In addition, the main criteria for the optimal choice and application of this or that type of controls and its relevance.